A proposal for the repatriation to Thailand of botanical data from the Royal Botanic Gardens, Kew - Pooma, Rachun (Thai Forest Bulletin (Botany), 2014)
Article 17 of the Convention on Biological Diversity obliges its 175 Parties to facilitate the exchange of information. taking into account the special needs of developing countries. and "where feasible. include repatriation of information". Biological data are necessary for the development of policies directed towards the conservation and sustainable use of a country's genetic resources. It is generally accepted the most important historical data are safer if conserved in developed countries with technology transfer and inkind assistance being preferable to the return of the original collections. An action plan, which would require additional financial support for its implementation. has been developed for the repatriation of taxonomic, historical, economic and conservation data, and a strengthening of collaboration between the Royal Botanic Gardens Kew and Thailand. Forest Herbarium (BKF) is suggested as the implementing agency and national herbarium in Thailand with collaboration from several biological institutions and Thai universities.